Host-Parasite list updating of Ciliates and fermentation in the digestive tract of wild miscellaneous herbivores in South Africa (RSA) - Booyse, D. G.; Dehority, B. A. (Zootaxa, 2017)
This article is dedicated to the Author, Burk Dehority, who became very ill with cancer. Fortunately he confirmed or corrected all identifications on ciliates in this article. This paper was 80% finished when he became ill. He unfortunately passed away in February 2016.